2022
DOI: 10.1007/s10914-021-09591-4
|View full text |Cite
|
Sign up to set email alerts
|

Maybe So, Maybe Not: Canis lepophagus at Hagerman Fossil Beds National Monument, Idaho, USA

Abstract: A canid dentary is described from the Pliocene Glenns Ferry Formation at Hagerman Fossil Beds National Monument, south-central Idaho, USA. The specimen possesses traits in alliance with and measurements falling within or exceeding those of Canis lepophagus. The dentary, along with a tarsal IV (cuboid) and an exploded canine come from the base of the fossiliferous Sahara complex within the monument. Improved geochronologic control provided by new tephrochronologic mapping by the U.S. Geological Survey-National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 96 publications
(147 reference statements)
0
1
0
Order By: Relevance
“…The distinctions of C. lepophagus and C. arnensis occurrences are not only geographical but also temporal: Tedford et al 27 suggested that C. lepophagus spans 4.9–1.8 Ma while C. arnensis is much younger (ca 2.2–1.6 Ma). Recently, some authors 47 noted that some North American occurrences referred to C. lepophagus should be referred differently (i.e., Canis aff. C. lepophagus , possibly a new species, and a Canis sp.…”
Section: Discussionmentioning
confidence: 99%
“…The distinctions of C. lepophagus and C. arnensis occurrences are not only geographical but also temporal: Tedford et al 27 suggested that C. lepophagus spans 4.9–1.8 Ma while C. arnensis is much younger (ca 2.2–1.6 Ma). Recently, some authors 47 noted that some North American occurrences referred to C. lepophagus should be referred differently (i.e., Canis aff. C. lepophagus , possibly a new species, and a Canis sp.…”
Section: Discussionmentioning
confidence: 99%